Social media integration in medical training: behavioral impact of short-form video creation as an active learning tool - De la Peña-Fernández, Lourdes; Zapata-Martínez, Irene (Frontiers in Medicine, 2025)
IntroductionThe rapid advancement of technology has transformed student behavior, increasing the demand for active learning strategies that integrate digital tools into medical education. Short-form video platforms such as TikTok offer an attractive format to enhance motivation and engagement among digital-native students. This study aimed to analyze the use of student-created videos in Radiation Oncology, evaluating their characteristics and, above all, students’ perceptions regarding their usefulness and their impact on competencies relevant to clinical practice.MethodsA cross-sectional study was conducted with 166 medical students at the University of Malaga. Of these, 148 (89.2%) voluntarily created short educational videos on course content. Student perceptions were measured through a validated 17-item questionnaire. Data were examined through a mixed-methods approach integrating quantitative and qualitative analyses.ResultsA total of 24 videos were produced. Nineteen videos (79.2%) were uploaded to TikTok. The questionnaire was completed by 144 students (97.3%): 91% expressed enthusiasm for innovative methodologies, 86% reported improved content assimilation, and 87% highlighted enhanced memory retention. Correlational analysis showed positive associations between interest in innovative methods and perceived research skills, memory retention, and satisfaction. Preference for traditional methods correlated negatively with memory retention and innovation interest. Teamwork (57%) and creativity were the most valued benefits; while editing and organizational demands posed the main challenges.ConclusionStudent-created short videos, particularly via TikTok, were well received and perceived as motivating, engaging, and supportive of key professional skills. This approach represents a promising complement to traditional medical education, although further controlled studies are required to confirm objective competency gains.